2022
DOI: 10.3390/su14148454
|View full text |Cite
|
Sign up to set email alerts
|

Higher Running Speed and Cardiovascular Endurance Are Associated with Greater Level of Academic Achievement in Urban Catalan Primary School Children

Abstract: The purpose of the present study was to determine the relationship between physical fitness and academic achievement in a sample of primary-school children. Data of 116 sixth-grade primary-school students (68 girls, 48 boys) from Barcelona (Catalonia, Spain) with a mean (SD) age of 11.4 years (0.4) was analyzed. To determine academic achievement, proficiency scores in the subjects Catalan language, Spanish language, English language, and Maths were derived from the Test de Compètencies Bàsiques. Physical fitne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…This was supported by Esteban-Cornejo et al ( 2014), who found that speed quality was correlated with academic performance, speci cally in mathematics and language courses 12 . Arboix-Alió et al ( 2022) also reported that students with higher performance in the Cooper and 20-m sprint tests had signi cantly better academic achievement in language and mathematics courses 14 . Additionally, muscle endurance exercises like sit-ups, standing long jumps, and sit-and-reach showed no correlation with academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by Esteban-Cornejo et al ( 2014), who found that speed quality was correlated with academic performance, speci cally in mathematics and language courses 12 . Arboix-Alió et al ( 2022) also reported that students with higher performance in the Cooper and 20-m sprint tests had signi cantly better academic achievement in language and mathematics courses 14 . Additionally, muscle endurance exercises like sit-ups, standing long jumps, and sit-and-reach showed no correlation with academic performance.…”
Section: Discussionmentioning
confidence: 99%